2009
DOI: 10.1684/mrh.2009.0176
|View full text |Cite
|
Sign up to set email alerts
|

Rumen epithelial cells adapt magnesium transport to high and low extracellular magnesium conditions

Abstract: A protein of~70-kDa was identified as a candidate Na + /Mg 2+ exchanger in rumen epithelial cells (REC). Melastatin-related Transient Receptor Potential 7 (TRPM7) and Magnesium Transporter 1 (MagT1) transcripts and, from them, encoded proteins were also detected. The regulation of these Mg transport pathways by extracellular [Mg] changes was the main focus of this study. Therefore, a 24-h pre-incubation of ovine REC in control (1.2 mM), low (0.12 mM)-Mg, and high (5 mM)-Mg medium was performed. Na + /Mg 2+ ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…From our review of the literature, MagT1 gene expression does not appear to be uniformly regulated in all tissues. Other studies have shown that in low concentrations of Mg 2+ , mammary epithelial MagT1 expression remains unchanged [20], while rumen epithelial cells actually downregulate MagT1 expression [17,18]. These results imply that there may be differential regulation of Mg 2+ and its transport machinery in various cell types.…”
Section: Discussionmentioning
confidence: 81%
“…From our review of the literature, MagT1 gene expression does not appear to be uniformly regulated in all tissues. Other studies have shown that in low concentrations of Mg 2+ , mammary epithelial MagT1 expression remains unchanged [20], while rumen epithelial cells actually downregulate MagT1 expression [17,18]. These results imply that there may be differential regulation of Mg 2+ and its transport machinery in various cell types.…”
Section: Discussionmentioning
confidence: 81%
“…Although not selective, these are the current pharmacological agents of choice for manipulating the Na ϩ /Mg 2ϩ exchanger functional activity (1,14,38,52). In a majority of studies (14,17,37,48,52), a Ϸ50% inhibition of Mg 2ϩ efflux has been reported after the application of imipramine (100 to 500 M).…”
Section: Discussionmentioning
confidence: 99%
“…It is long thought that a key element in this process is regulated Mg 2ϩ efflux either via an anion-dependent mechanism (36) or a putative Na ϩ /Mg 2ϩ exchanger (28). Evidence for the existence of both transport systems has been derived from functional studies with various cell types (1,2,14,17,24,38), but their molecular identity is unclear until today. However, within the last few years several genes (summarized in Ref.…”
mentioning
confidence: 99%
“…The A1-related Mg 2+ extrusion was not directly linked to anion (Cl − , HCO 3 − ) transport. However, it showed typical features of NME such as 1) activation by an increased [Mg 2+ ] i [26], 2) strict dependence on extracellular Na + [31, 32], 3) inhibition by imipramine and quinidine [33] and, 4) regulation via cAMP-dependent PKA [33]. Thus, unquestionably, A1 represents NME, the predominant Mg 2+ efflux system in mammalian cells [32, 34].…”
Section: Slc41a1 As a Na+/mg2+ Exchangermentioning
confidence: 99%